PENERAPAN PRINSIP PERADILAN UMUM PADA PENYELESAIAN PERKARA PIDANA PEMILIHAN KEPALA DAERAH - Gokma Toni Parlindungan s (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
Local elections or regional head elections are a means of implementing popular sovereignty in the regions. This is part of the development of the government administration system of the Republic of Indonesia experiencing various changes. The change in question is the principle of autonomy which means the freedom to regulate their own regions in each region. One of the challenges in carrying out this Pilada is a violation that results in a criminal offense. The formulation of this research is: 1) What is the form of the type of criminal case for the election of Regional Head in the general court environment? 2) how to apply the principle of simple, fast, low cost in the resolution of criminal cases in the election of Regional Heads 2020 in the general court environment. The research method used is normative juridical. The results showed, first there were 36 types of criminal cases in the election of regional heads in the general court environment, for this reason the Supreme Court issued a regulation of the Supreme Court of the Republic of Indonesia Number 1 of 2018 concerning Procedures for Settling Election and Election Criminal Acts. Second, the application of the principle of simple, fast, low cost in the resolution of criminal cases in the election of Regional Heads 2020 in the general court environment by combining several cases that are closely related. That is assessed from 36 types of post-conflict local election criminal acts that can be combined in one type in a practical and rational manner. This case can be resolved together with the plaintiffs.Keywords: Simple, Fast, Low Cost, Criminal Case, Local Election.